Efecto de la adición de minerales y vitaminas en la producción de huevos - Benavides Tintin, Wilman Gualther (2023)
This study was carried out in the Eastern District of the Bolívar parish, Pelileo Canton, Province of Tungurahua, with the general objective of evaluating the impact of different cores of vitamins and minerals added to the feed of Isa Brown birds during the rearing and starting phase. laying (12 to 22 weeks of age). 12 experimental units were used, each with five treatments and five repetitions, which represented a total of 300 birds. Over a 10-week period, different levels of minerals and vitamins in the birds' diet were compared. The treatments consisted of the addition of Suprafos-F, Selenium plus Vitamin E, vitamins and minerals (core), and calcium carbonate. The productive variables evaluated included weight gain, feed consumption, feed conversion, production percentage and egg diameter. The results revealed that the addition of Selenium + Vitamin E to the diet produced a slight increase in egg weight and diameter, as well as an improvement in the birds' laying breakdown. In addition, greater intake and weight gain, and better feed conversion were observed with this specific addition. However, the addition of vitamins and minerals in the different treatments did not have a significant effect on the evaluated parameters. These findings highlight the importance of including certain nutrients, such as selenium and vitamin E, in the diet of Isa Brown birds during the rearing and laying phase to improve their performance and productivity.